2009
DOI: 10.1073/pnas.0900040106
|View full text |Cite
|
Sign up to set email alerts
|

In-situ measurements of the mixing state and optical properties of soot with implications for radiative forcing estimates

Abstract: Our ability to predict how global temperatures will change in the future is currently limited by the large uncertainties associated with aerosols. Soot aerosols represent a major research focus as they influence climate by absorbing incoming solar radiation resulting in a highly uncertain warming effect. The uncertainty stems from the fact that the actual amount soot warms our atmosphere strongly depends on the manner and degree in which it is mixed with other species, a property referred to as mixing state. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

34
422
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(456 citation statements)
references
References 35 publications
34
422
0
Order By: Relevance
“…The physical and chemical properties (including density, shape, hygroscopicity, and refractive index) of these particle types are distinctly different from each other, influenced by various factors such as meteorological conditions and emission sources (e.g., Moffet and Prather, 2009;Zelenyuk et al, 2008). Therefore, it is expected that these particle types behave differently in the atmosphere and probably contribute differently to the environmental and climatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties (including density, shape, hygroscopicity, and refractive index) of these particle types are distinctly different from each other, influenced by various factors such as meteorological conditions and emission sources (e.g., Moffet and Prather, 2009;Zelenyuk et al, 2008). Therefore, it is expected that these particle types behave differently in the atmosphere and probably contribute differently to the environmental and climatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that optical properties of EC are sensitive to their physical (e.g., size and morphology) and chemical (e.g., composition, mixing state) properties (Moffet and Prather, 2009). While freshly emitted EC may contain limited coating, atmospheric aging such as coagulation with other particles, condensation of vapors, and in-cloud processing could cause EC to internally mix with other chemical species (e.g., Moffet and Prather, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While freshly emitted EC may contain limited coating, atmospheric aging such as coagulation with other particles, condensation of vapors, and in-cloud processing could cause EC to internally mix with other chemical species (e.g., Moffet and Prather, 2009). Cappa et al (2012) and Lan et al (2013) had observed a limited enhancement due to the mixing state of ambient EC, however, other studies confirmed the enhancement effect of internally mixing under various conditions (Wei et al, 2013;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved to be a powerful tool for analyzing the mixing state and formation mechanisms of aerosols in single particle levels (Gaston et al, 2010;Angelino et al, 2001;Moffet et al, 2004;Freney et al, 2006;Denkenberger et al, 2007;Moffet and Prather, 2009;Wang et al, 2009a;Yang et al, 2009). These accomplishments are extremely helpful to understand the impact of aerosols on the global climate.…”
Section: Introductionmentioning
confidence: 99%